PRINSIP-PRINSIP PERDAGANGAN MELALUI SISTEM ELEKTRONIK (PMSE) UNTUK MEMBERIKAN PERLINDUNGAN KONSUMEN - Deborah Cecilia (2022)
Trade activities in Indonesia over time are growing rapidly. The advancement of technology in trading activities formed a new trading system, namely e-commerce. E-commerce or trade with electronic systems plays a role in the progress of trade in Indonesia so that it has a good influence on the economy. The existence of technological advances in the trading system, has a tub impact and a negative impact on business actors and consumers. Thus, it is interesting to be further investigated so that the function of PMSE and its legal power for business actors who are not in accordance with PMSE. The research methods used in the research are qualitative based on statistical data obtained from consumer protection agencies related to complaints in e-commerce, news related to problems in ecommerce activities, and the success of regulations related to PMSE in the implementation of e-commerce. The results of this study show that the establishment of regulations in Indonesia that regulate electronic trade transactions can overcome consumer problems so as to provide maximum consumer protection. The conclusion of the settlement of the processing that occurs in PMSE requires the active role of business actors with consumers to carry out the principles of PMSE.